Emotional intelligence as the main indicator of the readiness of modern teachers for professional activity in the conditions of digitalization and inclusive education (Journal of Educational Sciences, 2021)
This article is devoted to the current topic of today – the need to develop emotional intelligence, which has a significant role in the professional activity of a teacher. Attention is focused on the fact that the developed emotional intelligence helps not only to solve the problem of psychological readiness for professional activity in the conditions of inclusive education, but also to overcome the barriers in the development of the didactic possibilities of digital educational resources, as well as the painless adapta- tion to the rapidly developing modern digital environment.The authors, based on the analysis of the research of foreign and domestic scientists, emphasize the peculiarity and importance of emotional intelligence, substantiate its role as the main indicator of teachers ‘ readiness for professional activity in the conditions of digitalization and inclusive education.On the basis of experimental work, the authors confirm that a highly developed emotional intel- ligence allows you to adequately respond to the resulting overload (emotional burnout), as well as the possibility of its correction, prevention. We used diagnostics to identify the emotional combustion syn- drome (SES) and est to determine the level of emotional intelligence of N. Hall, and also considered the development of emotional intelligence using specially organized methods, innovative technologies and programs. In the practical part of the study, 225 teachers from Kazakhstan took part.Key words: emotional intelligence, modern teacher, readiness, professional activity, digitalization, inclusive education.